Impact of the Covid-19 Pandemic on Liquidity, Profitability and Share Price (Study of LQ 45 Companies Listed on the Indonesia Stock Exchange 2018-2021 Period) - Mira Nurhikmat (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The Covid-19 pandemic has impacted various sectors of human life almost all over the world, including the economic sector. This study aims to test the impact of the two-year covid-19 pandemic on liquidity, profitability and stock prices. The current and quick ratios measure liquidity; profitability is measured by return on equity and net profit margin; the share price used is the closing share price at the end of the company's period. The research was conducted on companies that stayed at the LQ 45 position during the 2018-2021 period, and the method used was a paired sample t-test and a Wilcoxon signed rank test. The results of this study show that: a). neither the first year nor the second year of the pandemic had a significant impact on liquidity; b) The first year of covid-19 pandemic had a significant impact on profitability when measured by return on equity but did not have a significant impact when measured by net profit margin and the second year of the covid-19 pandemic did not have a significant impact on profitability; c). The first year or the second year of the pandemic did not impact the stock price.